Evaluating the hythane/water diesel emulsion dual fuel diesel engine characteristics at various pilot diesel injection timings. (2023) - Gopidesi, Radha Krishna; Premkartikkumar, S.R.
Abstract: In this experimental study was mostly focused on the impact of pilot diesel fuel Injection Timing (IT) on a dual fuel engine. The diesel engine was renewed in to dual fuel mode by injecting the Hythane20 (20% hydrogen and 80Methane) from the inlet manifold and Water in Diesel Emulsion 10 (10% water and 90% diesel WiDE10) as a primary fuel. Initially, the engine was operated at a constant Compression Ratio CR (18.5) and standard IT of 23°bTDC. Further, carried out the experimentation with retarded IT of 20°bTDC and Advanced IT of 26°bTDC. From the obtained results observed the higher Brake Thermal Efficiency (BTE) for 26°bTDC than the other. It is around 3.1 % higher and 6.45% lower Brake Specific Fuel Consumption (BSFC) than the diesel. It was also reported drastic reduction in smoke opacity 27.45% than the diesel fuel operation.